2004
DOI: 10.1016/s0002-9440(10)63274-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Human Autoantibody Response to α-Fodrin in Sjögren's Syndrome Reveals Novel Apoptosis-Induced Specificity

Abstract: Lymphocyte infiltration of salivary and lacrimal glands leading to diminished secretion and gland destruction as a result of apoptosis is thought to be pivotal in the pathogenesis of Sjögren's syndrome (SS). The cytoskeletal protein alpha-fodrin is cleaved during this apoptotic process, and a strong antibody (Ab) response is elicited to a 120-kd fragment of cleaved alpha-fodrin in the majority of SS patients, but generally not in other diseases in which apoptosis also occurs. Little is known about the anti-alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Alpha II-spectrin, besides being an important cytoskeletal protein, has been identified as a protein important to maintaining cell integrity and is found cleaved in the salivary glands cells of SS patients. Alpha II-spectrin has been proposed to be an autoantigen for Sjögren's syndrome [5,10,[45][46][47][48][49][50]; therefore, it is possible that the apoptotic cell death in the salivary gland cells of SS patients may somehow produce this autoantigen, but how this occurs is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alpha II-spectrin, besides being an important cytoskeletal protein, has been identified as a protein important to maintaining cell integrity and is found cleaved in the salivary glands cells of SS patients. Alpha II-spectrin has been proposed to be an autoantigen for Sjögren's syndrome [5,10,[45][46][47][48][49][50]; therefore, it is possible that the apoptotic cell death in the salivary gland cells of SS patients may somehow produce this autoantigen, but how this occurs is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The glands most affected in SS include the tear glands and the salivary glands. Histological studies indicate an increased infiltration of immune cells is present in the parotid and submandibular salivary gland epithelial cells of SS patients [9][10][11]. Activated immune cells secrete proinflammatory cytokines such as tumor necrosis factor alpha (TNF-alpha), interferon-gamma (IFN-gamma) and Fas ligand (FasL) and increased secretion of inflammatory cytokines has been associated with salivary gland cell death in SS patients [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The autoantigen, α-fodrin, has been postulated to be involved in the autoimmune responses leading to glandular destruction of lacrimal and salivary glands. 9 The presence of α-fodrin autoantigen has been found in 93% of primary SS patients, 10 and it has been reported that α-fodrin is a specific and sensitive marker for SS diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, salivary gland cells from patients with SS exhibit greater expression of Fas receptor (CD95), a death domain-containing member of the TNF receptor superfamily, which mediates apoptosis triggered by Fas ligand (FasL)-expressing lymphocytes [7]. Apoptosis in salivary tissue can be induced in vitro by Tumor Necrosis Factor (TNF): TNF, previously known as TNF-α, is a pleiotrophic cytokine produced by immune cells in response to infection, environmental challenges and/or other danger signals [8]- [10]. As an early pro-inflammatory cytokine, TNF stimulates production of various cytokines, chemokines, coagulation factors, and other inflammatory mediators, and up-regulates the expression of adhesion molecules [11].…”
Section: Introductionmentioning
confidence: 99%